2006
DOI: 10.1074/jbc.m510827200
|View full text |Cite
|
Sign up to set email alerts
|

Mutated Yeast Heat Shock Transcription Factor Activates Transcription Independently of Hyperphosphorylation

Abstract: The homotrimeric heat shock transcription factor (HSF) binds to the heat shock element of target genes and regulates transcription in response to various stresses. The Hsf1 protein of Saccharomyces cerevisiae is extensively phosphorylated upon heat shock; a modification that is under positive regulation by its C-terminal regulatory domain (CTM). Hyperphosphorylation has been implicated in gene-specific transcriptional activation. Here, we surveyed genes whose heat shock response is reduced by a CTM mutation. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 53 publications
(73 reference statements)
1
51
0
Order By: Relevance
“…Temperatureresistant mutations near the DBD enable Hsf1 lacking its C-terminal AD to activate transcription (Hashikawa et al 2006). These suppressors implicate the DBD in mediating the response, as did single point mutations that constitutively enhanced transcription (Bulman et al 2001).…”
Section: Hsf1 Regulation Through Conformational Changementioning
confidence: 99%
See 2 more Smart Citations
“…Temperatureresistant mutations near the DBD enable Hsf1 lacking its C-terminal AD to activate transcription (Hashikawa et al 2006). These suppressors implicate the DBD in mediating the response, as did single point mutations that constitutively enhanced transcription (Bulman et al 2001).…”
Section: Hsf1 Regulation Through Conformational Changementioning
confidence: 99%
“…The N-and C-terminal ADs activate different sets of genes in the Hsf1 regulon during heat shock (Eastmond and Nelson 2006). Stress-induced activation is accompanied by Hsf1 hyperphosphorylation, but whether it is important for activation or for return to an inactive state is unclear (Sorger 1990;Jakobsen and Pelham 1991;Hoj and Jakobsen 1994;Hashikawa et al 2006).…”
Section: Hsf1 Regulation Through Conformational Changementioning
confidence: 99%
See 1 more Smart Citation
“…Mammalian, fly, and plant HSFs have just a single trans-activation domain, whereas the HSFs of yeasts possess two distinct trans-activation domains: one close to the amino terminus and the other adjacent to the carboxy terminus (NTA and CTA, respectively). Loss of the C-terminal (CT) domain of Hsf1 (sequences 583 to 833, containing the CTA and modulator sequences) leads to a compromised induction of certain genes, but not others, in response to heat shock (8,16,18,35,43,45). It also causes loss of the ability to grow above about 35°C, revealing that gene expression directed by the Hsf1 CT domain is required for yeast to grow at high temperature.…”
mentioning
confidence: 99%
“…Although the molecular weight of the peptides recognized do not precisely correspond to the molecular weight of the predicted EhHSTF, in the literature has been reported that these proteins may occur postranslational modifications as phosphorylation provoking changes in their molecular weights [36]. Perhaps, have been reported that the HSTF requires being homotrimerized to binds to the HSE [37].…”
Section: Discussionmentioning
confidence: 99%